Methylammonium Bismuth Iodide as a Lead‐Free, Stable Hybrid Organic–Inorganic Solar Absorber. Issue 8 (18th January 2016) - Hoye, Robert L. Z.; Brandt, Riley E.; Osherov, Anna; Stevanović, Vladan; Stranks, Samuel D.; Wilson, Mark W. B.; Kim, Hyunho; Akey, Austin J.; Perkins, John D.; Kurchin, Rachel C.; Poindexter, Jeremy R.; Wang, Evelyn N.; et al.
Abstract: Methylammonium lead halide (MAPbX3 ) perovskites exhibit exceptional carrier transport properties. But their commercial deployment as solar absorbers is currently limited by their intrinsic instability in the presence of humidity and their lead content. Guided by our theoretical predictions, we explored the potential of methylammonium bismuth iodide (MBI) as a solar absorber through detailed materials characterization. We synthesized phase‐pure MBI by solution and vapor processing. In contrast to MAPbX3, MBI is air stable, forming a surface layer that does not increase the recombination rate. We found that MBI luminesces at room temperature, with the vapor‐processed films exhibiting superior photoluminescence (PL) decay times that are promising for photovoltaic applications. The thermodynamic, electronic, and structural features of MBI that are amenable to these properties are also present in other hybrid ternary bismuth halide compounds. Through MBI, we demonstrate a lead‐free and stable alternative to MAPbX3 that has a similar electronic structure and nanosecond lifetimes. Abstract : Call me MA‐Bi‐I ! A lead‐free alternative to hybrid lead perovskites is explored for solar cells: methylammonium bismuth iodide (see figure). This material exhibits higher air stability than hybrid lead perovskites, while demonstrating optoelectronic properties promising for solar absorbers.